2022
DOI: 10.3390/ijerph192417034
|View full text |Cite
|
Sign up to set email alerts
|

Motivations Influencing Alipay Users to Participate in the Ant Forest Campaign: An Empirical Study

Abstract: As one of the largest payment platforms in China, Alipay, launched a green behavior project called Ant Forest. The purpose of taking this initiative by Alipay is to make the world greener. This mobile application has motivated many users to plant millions of trees. However, minimal studies have been conducted to empirically disclose the factors that motivate Alipay users to participate in Ant Forest. A mixed-method approach is used to examine the factors influencing Alipay users to participate in Ant Forest an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…In addition, gamification showed a significant negative moderating effect on the relationship between trendiness and consumer-brand engagement in Ant Forest. While gamified platforms have proven more appealing to novelty-seeking consumers, this finding does not apply to all consumers [ 93 ], since most users select Ant Forest because it is considered to be an inevitable trend through which they can really engage in environmental protection in a realistic way [ 94 ]. In addition, this popular trend runs counter to the massive virtual rewards provided by gamification in Ant Forest [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gamification showed a significant negative moderating effect on the relationship between trendiness and consumer-brand engagement in Ant Forest. While gamified platforms have proven more appealing to novelty-seeking consumers, this finding does not apply to all consumers [ 93 ], since most users select Ant Forest because it is considered to be an inevitable trend through which they can really engage in environmental protection in a realistic way [ 94 ]. In addition, this popular trend runs counter to the massive virtual rewards provided by gamification in Ant Forest [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the first step, the instrument was checked for normality, then the external model was tested, and once it was confirmed that the external model was suitable, Smart PLS3 was used to analyze the internal model after it had been confirmed that the external model was suitable. (Habes, Al-Adwan, et al, 2022;Habes, Ali, et al, 2022;Wang et al, 2022).The procedures that have been followed for analyzing the collected data are mentioned in the analysis portion.…”
Section: Methodsmentioning
confidence: 99%
“…Survey questionnaires will be circulated online among the target population to collect responses. Partial Least Squares Structural Equation Modeling (PLS-SEM) method has been employed to assess the relationship between independent, dependent and outcome variables (Al Olaimat et al, 2022;Habes et al, 2022;Habes, Alghizzawi, et al, 2023;Tahat et al, 2022;Wang et al, 2022). Green entrepreneurial inclinations will be taken as dependent variable for this research, while perceived educational support, perceived concept development support, university green entrepreneurial support, perceived business development support, and perceived institutional support were taken as independent variables, whereas sustainable competencies were taken as outcome variable (Habes, Ali, & Pasha, 2021;Habes, Ali, Khalid, et al, 2021;Salloum et al, 2019).…”
Section: Methodsmentioning
confidence: 99%